Public Policy and Financial Regulation in Housing Sector (Case Study: One Million Houses and KPR FLPP) - Maria Dellarosawati Idawicaksakti; Monica Dianrosawati Itaratnasari; Raden Aswin Rahadi (School of Industrial and System Engineering, Telkom University, 2022)
During Jokowi’s tenure, a lot of programs and policies that focusing on housing sector were built by him. Package of Economic Policy XIII is one of many policy’s package that Jokowi develop for managed housing of people who have low income (MBR) with target that chosen is built one million houses. The lack of availability of housing for low-income people, is one of the reasons for the policy package. In this research, author used qualitative method to analyst the phenomenon. The results of this study are the high rate of housing backlogs, the difficulty of obtaining housing at affordable prices, and discussing KPR schemes in Indonesia. The existence of these government programs does not significantly eliminate the phenomenon of housing a backlog. In addition, the existence of the program must be accompanied by high supervision from the government and accompanied by laws that bind violators.